Green Brand Image, Green Perceived Quality, Green Trust, Green Purchase Intention.: PENGARUH GREEN BRAND IMAGE, DAN GREEN PERCEIVED QUALITY TERHADAP GREEN PURCHASE INTENTION MELALUI GREEN TRUST (STUDI PADA KONSUMEN TUPPERWARE DI CILEGON) - Kayubiyanto, Anggit yoebrilianti; Nafiuddin, Nafiuddin; Putri, Visensia (Universitas Serang Raya, 2024)
Society globally is starting to realize environmental changes due to global warming. With the phenomenon regarding the environment, it is interesting to research and this research aims to explain the influence of green brand image and green perceived quality on green trust and green purchase intention in Tupperware products in Cilegon City with green trust as a mediating variable. This research was conducted in Cilegon City with a sample size of 70 Tupperware user respondents. The sample was determined using a non-probability sampling model, with accidental sampling technique. The data that has been collected is processed using path analysis techniques using SPSS 25 for Windows. The results of this research show that partially that green brand image has a significant and positive effect on green trust and green purchase intention, green trust has a significant and positive effect on green purchase intention and then green trust is unable to mediate the effect of green brand image on green purchase intention, while green trust is able to mediate the influence of green perceived quality on green purchase intention